ENGINEERING PEDAGOGY: METHODOLOGICAL ISSUES - article Editorial (Moscow Polytechnic University, 2017)
In the framework of Tatarstan Gas and Petrochemical Forum (Kazan', September 7-8) a round table discussion "Engineering Pedagogy: Methodological Issues" was held. The discussion was organized by Kazan National Research Technological University and the Editorial Board of the journal Vysshee obrazovanie v Rossii (Higher Education in Russia). The participants were the leading researchers and experts in engineering education and engineering pedagogy.